2017
DOI: 10.3390/app7101043
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Thermoelectric Properties of TiO2/Cu2SnSe3 Composites

Abstract: Thermoelectric (TE) materials are a kind of energy material which can directly convert waste heat into electricity based on TE effects. Ternary Cu 2 SnSe 3 material with diamond-like structure has become one of the potential TE materials due to its low thermal conductivity and adjustable electrical conductivity. In this study, the Cu 2 SnSe 3 powder was prepared by vacuum melting-quenching-annealing-grinding process. The nano-TiO 2 particles were introduced into the Cu 2 SnSe 3 matrix by ball milling. Spark pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…5 Comparison of ZT values before and after doping of different oxides into different TE materials. [1][2][3][4][5][6][7][8][9][10] sintering (SPS) processes. Although the B 2 O 3 second phase boundary scattered carriers, resulting in a decrease in mobility, the increase in resistivity was acceptable.…”
Section: Second-phase Precipitationmentioning
confidence: 99%
“…5 Comparison of ZT values before and after doping of different oxides into different TE materials. [1][2][3][4][5][6][7][8][9][10] sintering (SPS) processes. Although the B 2 O 3 second phase boundary scattered carriers, resulting in a decrease in mobility, the increase in resistivity was acceptable.…”
Section: Second-phase Precipitationmentioning
confidence: 99%
“…Rigid, thermally, and electrically impermeable inclusions such as oxide nanoinclusions have a maximum effect on the thermal and electrical carriers and enhance the mechanical stability . There are various oxide-based nanoinclusions such as TiO 2 , , WO 3 , ,, ZrO 2 , ,,,,,,, Al 2 O 3 , , CeO 2 , , Y 2 O 3 , , SiO 2 , ,, ZnO, ,,,, SrTiO 3 , SnO 2 , Yb 2 O 3 , NiO, and reduced graphene oxide to improve the thermoelectric performance of the composites. Here, α is expressed as ∝ = γ – ln­( n ), where γ is the scattering factor and n is the carrier concentration; after the addition of oxide nanoinclusions, γ enhances and n decreases to increase the α in two ways.…”
Section: Classification Of Nanoinclusionsmentioning
confidence: 99%
“…Furthermore, recent studies have reported a promising compositing strategy to achieve a further reduction in the lattice thermal conductivity of Cu 2 SnSe 3 -based materials. Recently, researchers have focused on developing Cu 2 SnSe 3 composites by introducing metal oxides, , chalcogenides, and other additives , to enhance phonon scattering. Moreover, in situ formed Ag 2 S nanoprecipitates in p-type Ag-doped PbS have been proven effective in reducing the grain boundary barrier height, thus improving the carrier transport .…”
Section: Introductionmentioning
confidence: 99%